Family Rites in Podhale - Lehr, Urszula (Institute of Archaeology and Ethnology Polish Academy of Sciences, 2014)
Traditional and contemporary rituals presented in the article, are examples of a specific type of functioning of families and rural communities in the context of the customs and rituals referring to the rites of previous generations. The transformations associated with the elimination and modification of old elements of rituals and introduced successively new customary formulas did not affect significantly on the basic scheme of scenario of celebrated phases of human life, which have manifested themselves through multiple verbal and non-verbal symbolism. Regardless of the style of contemporary family ceremonies, accumulating and imposing a specific rite of the created highland cultural phenomenon, it has still remained recognizable designatum, clearly emphasizing regional distinctiveness of Podhale, which is identical with the cultural identity of the inhabitants
ill. ; 24 cm
Keywords: family rites; rituals; ceremonial forms; Podhale; highlanders; tradition; folk; wedding; funeral; identity